Closing the Legislative Experience Gap: How a Legislative Law Clerk Program Will Benefit the Legal Profession and Congress - Dakota S. Rudesill (Washington University Law Review, 2010)
In this gloomy hiring season there is at least one increasingly bright spark, one that may light the way to a new kind of apprenticeship experience for future participants in the highly competitive national clerkship market. Pending in the U.S. Senate is House Bill 151, and its Senate companion, Senate Bill 27, that would for the first time create a law clerk program in the U.S. Congress analogous to other legal apprenticeship opportunities. Prospects for the program are encouraging, thanks to the House’s overwhelming 381–42 vote in March 2009. I argue that closing the legislative experience gap ultimately will benefit the profession and Congress by helping both of these key legal players better understand — and take more seriously — an under appreciated reality: legislative work is legal work. I conclude by refuting objections, and encouraging lawyers to engage with Congress in support of the bill.
Keywords: Law clerks; Legislative bodies; Practice of law; United States. Congress